2006
DOI: 10.1523/jneurosci.3292-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

RTP801 Is Elevated in Parkinson Brain Substantia Nigral Neurons and Mediates Death in Cellular Models of Parkinson's Disease by a Mechanism Involving Mammalian Target of Rapamycin Inactivation

Abstract: The molecules underlying neuron loss in Parkinson's disease (PD) are essentially unknown, and current therapies focus on diminishing symptoms rather than preventing neuron death. We identified RTP801 as a gene whose transcripts were highly induced in a cellular model of PD in which death of neuronal catecholaminergic PC12 cells was triggered by the PD mimetic 6-OHDA. Here, we find that RTP801 protein is also induced in this and additional cellular and animal PD models. To assess the relevance of these observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
213
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(227 citation statements)
references
References 47 publications
12
213
1
1
Order By: Relevance
“…Attenuation of mTOR signaling has been reported in several neurodegenerative diseases, including Parkinson's disease (Inoki et al, 2005). Neurotoxins, such as 6-OHDA, MPTP, and rotenone, block the activation of mTOR signaling in neuronal cultures and in animals (Malagelada et al, 2006). In fact, we show here that mitochondrial damage induced by MPTP treatment results in a significant decrease of mTOR activity and inhibition of rRNA transcription.…”
Section: Discussionsupporting
confidence: 57%
“…Attenuation of mTOR signaling has been reported in several neurodegenerative diseases, including Parkinson's disease (Inoki et al, 2005). Neurotoxins, such as 6-OHDA, MPTP, and rotenone, block the activation of mTOR signaling in neuronal cultures and in animals (Malagelada et al, 2006). In fact, we show here that mitochondrial damage induced by MPTP treatment results in a significant decrease of mTOR activity and inhibition of rRNA transcription.…”
Section: Discussionsupporting
confidence: 57%
“…Our past studies have shown that the stress-responsive protein RTP801 is substantially induced in multiple cellular models of PD, in an animal model of PD and in dopaminergic neurons of patients with PD (Ryu et al, 2002;Malagelada et al, 2006). RTP801 over-expression is sufficient to promote neuron death and we have reported that this protein is required for neuron death in cellular models of PD .…”
Section: Discussionmentioning
confidence: 84%
“…RTP801 is induced by stresses including DNA damage, oxidative stress, hypoxia, ER stress and energy depletion (Ellisen et al, 2002;Shoshani et al, 2002;Wang et al, 2003;Sofer et al, 2005) that have been raised as causes of neuron degeneration in PD (Marras and Lang, 2008). RTP801 can be pro or antiapoptotic and in neuronal cells promotes death (Shoshani et al, 2002;Malagelada et al, 2006). We found that multiple PD mimetics (6-OHDA, MPPϩ and rotenone) induced RTP801 in neuronal cells and that it mediated death in each case .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Increased REDD1 expression in neurodegenerative diseases such as Parkinson´s and Alzheimer´s disease leads to permanent inhibition of mTOR and thereby cellular death [22,23]. On the contrary, reduced REDD1 expression and constitutive mTOR signalling is found in cancer patients [16,18].…”
Section: Introductionmentioning
confidence: 99%